2017
DOI: 10.1257/app.20150548
|View full text |Cite
|
Sign up to set email alerts
|

Wealth Heterogeneity and the Income Elasticity of Migration

Abstract: How do income shocks affect international migration flows from poor countries? Income growth not only increases the opportunity cost of migration but also eases liquidity constraints. I develop a method to separate these countervailing individual effects and identify the overall income elasticity of migration. Using new administrative and census data from Indonesia, I find that positive agricultural income shocks increase labor emigration flows, particularly in villages with relatively more small landholders. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 65 publications
12
113
2
Order By: Relevance
“…Our first stage showed that individuals are more likely to engage in internal migration in response to bad rainfall; poorer individuals may respond this way due to an insurance motive (Kleemans, ), which could lead to our empirical results. Alternatively, richer people may respond to poor rainfall due to lower opportunity costs at home (Bazzi, ), which would render the patterns here even more striking. In Table , we test whether contemporaneous rainfall shocks also create a pool of migrants who are less educated compared to most migrants by restricting our sample to migrants and regressing an indicator variable for high education on origin rainfall measures.…”
Section: Heterogeneity By Skill Levelmentioning
confidence: 99%
“…Our first stage showed that individuals are more likely to engage in internal migration in response to bad rainfall; poorer individuals may respond this way due to an insurance motive (Kleemans, ), which could lead to our empirical results. Alternatively, richer people may respond to poor rainfall due to lower opportunity costs at home (Bazzi, ), which would render the patterns here even more striking. In Table , we test whether contemporaneous rainfall shocks also create a pool of migrants who are less educated compared to most migrants by restricting our sample to migrants and regressing an indicator variable for high education on origin rainfall measures.…”
Section: Heterogeneity By Skill Levelmentioning
confidence: 99%
“…Micro-level studies using individual and household data, and employing both cross-sectional and panel data approaches, have been often applied to countries highly dependent on the agricultural sector as the main source of income, such as Ecuador [86,87], Nigeria [76,88], Bangladesh and Ethiopia [53,83,89], Indonesia [68,90], and Tanzania [73].…”
Section: Micro-studies At the Individual And Household Levelmentioning
confidence: 99%
“…and/or conflicts (see, among others, Paxson 1992;Munshi 2003;Miguel et al 2004;Giles and Yoo 2007;Yang and Choi 2007;Deschênes and Moretti 2009;Maccini and Yang 2009;Barrios et al 2010;Brückner 2010;Feng et al 2010;Pugatch and Yang 2010;Brückner and Ciccone 2011;Ciccone 2011;Dell et al 2012;Bazzi 2014). We add to this literature by demonstrating that temporary weather shocks are also a powerful predictor of immigrants' legal status.…”
mentioning
confidence: 80%
“…Our first strategy is based on the idea that higher levels of rainfall induce a positive and unexpected temporary income shock that allows those who would like to emigrate to cover the cost of an immediate illegal migration (rather than applying for the lengthy legal pathway). Drawing on earlier evidence that shows that weather conditions affect income in developing countries (see, e.g., Wolpin 1982;Paxson 1992;Miguel et al, 2004;Barrios et al, 2010;Brückner and Ciccone 2011;Bazzi 2014) we use weather shocks at the time of emigration as an instrument for legal status. We illustrate that these shocks have a strong effect on income in the emigration countries we consider, and that higher than average levels of rainfall are strong predictors of immigrants' current legal status.…”
Section: Introductionmentioning
confidence: 99%